Status of cholesterol and lipase in Ascaridia galli nematode parasite parasitizing Domestic Fowl Host - R. D. Barde, Govind H. Balde* and (Recent Research in Science and Technology, 2011)
In A. galli Schrank [17], Freeborn, [8] most of the lipids are located in the hypodermis, especially in the lateral cords, in the non-contractile part of the muscle cells, in the intestine of host. Cholesterol and lipase has a variety of functions in tissues. Cholesterol occurs in association with proteins, carbohydrates, lipo proteins and glycolipids. They are major structural components of cell membranes. Lipids include simple lipids, such as fats and oils and derived lipids such as fatty acids, cholesterol and ketone bodies.